Seven Student Motivations for Choosing the Department of Early Childhood Teacher Education in Higher Education - Elkhaira, Indana; Audina B.P., Nidya; Engkizar, Engkizar; K., Munawir; Arifin, Zainul; Asril, Zainal; Syafril, Syafrimen; Brita Deborah Mathew, Ingrid (Al-Athfal: Jurnal Pendidikan Anak, 2020)
Choosing a career as an Early Childhood Education Teacher is both challenging and joyful. Not everyone is interested in this profession except for those who have strong motivation. This study aims to identify students’ exact motivation to select the Early Childhood Education Department at Public University. This study uses combined qualitative and quantitative methods (exploratory mixed methods design). Sources of qualitative data were taken from twenty informants through in-depth interviews and analyzed using NVivo 10 analysis software, while sources of quantitative data were taken from a hundred correspondents and analyzed using SPSS 20 software. Both qualitative and quantitative data analyses showed that students have seven motivations to select the Early Childhood Education Department. Those seven motivations are: i) parents encouragement (81%); ii) job opportunities after graduation (83%); iii) loving kids (85%); iv) teaching is a noble profession (100%); self-will (70%); vi) the choice to be a teacher (76%); and vii) Early Childhood Education is not difficult, but joyful (80%). The study has successfully revealed seven students’ motivations for selecting the Early Childhood Education Department at Public University. This study’s results can be used as preliminary data for subsequent researchers to examine this problem in different contexts and issues. This study’s findings need to be continued by the next researcher by examining the correlation between motivational aspects with various other variables. However, this data can also be used as an initial reference for examining the issues and problems in different contexts.